A Phase Distribution Design Method for Phased Arrays Multibeam Independently Generating and 3-D Scanning - Dong Wang; Yu-Li Wu; Bao-Quan Jin; Peng Jia; Dong-Mei Cai (IEEE Photonics Journal, 2014)
This paper reports the realization of a phase distribution design method for phased arrays multibeam independently generating and 3-D scanning. The phase distribution design method inherits the projection optimization idea from the generalized adaptive-additive algorithm; however, a striking difference here is that the iteration plane is not just one but multiple, which means the method promises to be not only suitable for creating phase distributions for multibeam independently lateral scanning but capable of creating phase distributions for independently axial scanning as well. Both simulations and experiments were conducted to investigate the performance of the method; simulation agrees with experimental results, which validates the effectiveness of the method proposed. The technique described in this paper could provide a promising convenient multibeam generating and 3-D scanning for ladar, laser weapons, laser micromachining, etc.